HAEMATOLOGICAL RESPONSE OF Clarias gariepinus (BURCHELL, 1822) FINGERLINGS TO VARYING LEVELS OF BETAINE/B – GLUCAN FEED ADDITIVE - Ali, Mark Eka; Sogbesan, Olukayode Amos; Abubakar, Kotos Abdulrahman; Salisu, Sylvia Ali (FUDMA JOURNAL OF SCIENCES, 2025)
This study was designed to evaluate the haematological response of Clarias gariepinus fingerlings to varying levels of betaine/ glucan feed additive. Combination of betaine/ glucan as feed additive was included into formulated feed with 40% crude protein at; 0.0g/100g (BBG0 i.e. control), 0.325g/100g (BBG1), 0.75g/100g (BBG2), 1.125g/100g (BBG3) and 1.50g/100g (BBG4) in triplicates. Feed was fed to C. gariepinus fingerlings (n = 300, 10.00.00g) in fifteen (15) plastic tanks (n = 20) at a fixed feeding rate of 3% body weight twice daily between the hours of 8:00 9:00am and 4:00 5:00pm at regular interval and adjusted after every two (2) weeks of sampling for a period of twelve (12) weeks. Blood samples were collected from three (3) fish at the commencement and also from three (3) fish from each treatment and the control at the termination of the feeding trial for hematological analysis. Data collected was statistically analysed using one - way analysis of variance (ANOVA) at P = 0.05. PCV values (41.33.3 42.71.9 %), RBC (2.560.6 106 2.820.1 106 dL-1), WB (249.814 103 266.5 16 103 dL-1), Hb (12.12.2 13.52.4 gdL-1), platelet (27.751.5 104 29.201.4 104 dL-1), MCV (136.77.9 155.111.0 m-3), MCH (40.72.2 50.12.5 gL-1), MCHC (31.22.1 33.12.6 gdL-1), neutrophil (32.103.2 33.702.0 %), lymphocyte (95.76.4 97.68.3 %) and monocytes (2.850.2 3.700.3 %) respectively were recorded. Combination of betaine/ glucan feed additive at varying levels used in this study did not result in statistically significant changes (p>0.05) in haematological responses of C. gariepinus.
Keywords: Haemoglobin; Lymphocytes; Monocytes; Packed Cell Volume; Platelet